Ashanti Proverbs (The Primitive Ethics of a Savage People) Translated From the Original With Grammatical and Anthropological Notes - Rattray, R.S. (Oxford University Press, 1916)
IN preparing this volume, to which he has asked me to contribute a preface, Mr. Rattray has performed a considerable service to those of us who are interested in the Tshis-peaking people of the Gold Coast, or who are concerned in the administration of their affairs. He has blazed for us a track through a wilderness which has so far been very imperfectly explored, and has thereby opened the way to further discoveries. Much has been said and written concerning the difficulty which the European mind usually experiences in comprehending the mentality of Orientals, but it is probable that the difficulties which beset a student of West African thought are far greater than any which are experienced in Asia. Orientalists of many nations have been engaged for centuries in interpreting the East to the West, and their efforts, more especially during the past fifty years, have been attended by a certain measure of success. All the great literatures of Asia are to-day accessible to European scholars, and familiarity with Oriental languages is now common. The philosophies of Asia have not failed to make their strong appeal to many Europeans, in spite of the fact that they are, in the main, distinctive products, dissimilar from anything which the West has evolved on its own account. In the same way, democratic theories of government, which may regarded as being in some sort the exclusive product of the European intellect, have recently
Heritage
Keywords: Proverbs; Ethics; Anthropological Notes